If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 3) = x + 6(x + 1) Reorder the terms: 2(3 + 5x) = x + 6(x + 1) (3 * 2 + 5x * 2) = x + 6(x + 1) (6 + 10x) = x + 6(x + 1) Reorder the terms: 6 + 10x = x + 6(1 + x) 6 + 10x = x + (1 * 6 + x * 6) 6 + 10x = x + (6 + 6x) Reorder the terms: 6 + 10x = 6 + x + 6x Combine like terms: x + 6x = 7x 6 + 10x = 6 + 7x Add '-6' to each side of the equation. 6 + -6 + 10x = 6 + -6 + 7x Combine like terms: 6 + -6 = 0 0 + 10x = 6 + -6 + 7x 10x = 6 + -6 + 7x Combine like terms: 6 + -6 = 0 10x = 0 + 7x 10x = 7x Solving 10x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 10x + -7x = 7x + -7x Combine like terms: 10x + -7x = 3x 3x = 7x + -7x Combine like terms: 7x + -7x = 0 3x = 0 Divide each side by '3'. x = 0 Simplifying x = 0
| 7y+3x=58 | | -3/7(2)-2=y | | 7+63y= | | 6p-8p+-5=-17 | | 55m+5= | | 7x+4+5x+3+2+5=180 | | .80(5-20x)=-44 | | (-3)^5/(-3)^8 | | 102=-3(6n-4) | | h(x)=(2x+5)(3x-1) | | 7^5/7^3 | | (-4)^8/(-4)^4 | | 8^4/8^0 | | -6x^2+11-13=0 | | (-3)^6/(-3)^8 | | (-8w+8)-(w-2)= | | 8cosx=6 | | -6w-(-4z+5w)+7z= | | 78x+31=90 | | 78x+31=180 | | y=-1+28x-171 | | (-2-n)+(6n-7)= | | 5+2(9x-4)=4x+7 | | 2(6-5x)+6=8-5x | | 9/5=x/20 | | y=-4x+28x-171 | | 40/64=10/t | | 25/12x=30 | | -11-3(2*-11-7)= | | 2(2x-9)-5=2(x-5)-3 | | 25-12x=30 | | 7x-(2x+17)=18 |